An Analysis of English Tests at Pilot International Standard School in 2010/2011 – 2011 /2012 Academic Year - Afriyanti, Rika (TELL - US JOURNAL, 2015)
This research was based on the phenomenon happened in one of the Pilot International Standard Schools (RSBI) in Padang in which most of the students’ score at grade VIII could not fulfill the minimum standard of achievement (KKM) in English semester test designed by the Central government in 2010/2011 academic year. Therefore, this research was aimed at analyzing whether the test designed by the Central government contributes to the students’ failure or not. However, the researcher did not only analyze the test designed by the Central Government but also analyse the tests designed by the teachers. The researcher did qualitative item analysis which focused on analyzing the format of the test items (stem, options and distractors), content validity and face validity. This research was conducted based on descriptive method and there were two sources of data of this research: the document of English tests and the respondents of interview. The result of this research is the test designed by the Central Government in 2010/2011 academic year is the better one, because almost all the items could fulfill all the criteria in designing multiple-choice test. Meanwhile, the Mid-test designed by the teachers in 2010/2011 academic year indicated as the poor one. There are some criteria that could not be fulfilled by all the tests. They are; the curriculum demand, the relevance between the assessment plan/blue-print with the items, writing the stem and many items are not paraphrased. Therefore, it can be interpreted that the teachers still do not have enough competence in designing the test which based on National standard and the government also, because the researcher still found the test items designed by the central government that could not fulfill the criteria in writing a good multiple-choice test.